(3TQM GddHGH aj Yde GdEYQGHs - (3bWH GdOjf eMeO Hf eSYhO Hf eMehO Hf CHj GdaJM GdZGdj GdTbGQ GdSjQGajs; (3eMeO Hf eMeO Hf CMeO, JGL GdOjf GdCSaQGjjfj,J (B684 (3g` s ((3UGYO Hf SdjeGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG Edi eYQaI EYLGR GdbQBf cJGH GddHGH aj GdfMh cJGH dG jNai ebOGQg s
(3BNQgG (B:s
(3hGdUaI bO Jchf GSe aGYd EPG cGf GdehUha fcQI hEP bO hajfG HeG hYOfG s
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3JYGhQ YdjgG CcKQ ef fGSN BNQge UGYO Hf SdjeGfs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs